Inconstitucionalidad de los antecedentes penales, al aplicar el dictamen abstentivo y el auto de sobreseimiento - Hurtado Gallegos, Angélica Elizabeth (Machala, Utmachala, 2023)
The objective of this research is to demonstrate the global problem suffered by Persons who were Deprived of Liberty, for some crime or misdemeanor they committed, producing for them the tragedy of not being able to obtain or maintain themselves, within the labor market, for possessing criminal records that are easily reflected in the State platforms, it should be said, that the qualitative-quantitative methodology has been sponsored, based on the interview; the results have been granted interdisciplinary to us by Persons Deprived of Liberty, Authorities of Ecuador, so far this problem continues to cause a lot of pain, because it is difficult to obtain a decent and safe job, even if they have third, fourth or fifth level titles, being in the highest degrees of discredit for having been in a prison, must disappear from the State platforms, since, every person very easily consults and stigmatizes them with the descriptions of criminals, the social system does not allow them to be reintegrated, reintegrated into society, in order to survive from the fruit gained, by prohibiting them from having an employment relationship, being absorbed by the large criminal structures, which capture them by giving them small and large assignments that generate a payment, making their lives more bearable, and therefore again , they see themselves back in the underworld of crime and delinquency
El objetivo de investigación es demostrar la problemática global que sufren las/os Personas que estuvieron Privadas de Libertad, por algún delito o contravención que cometieron, produciéndolesde por vida la tragedia de no poderobtener nimantenerse,dentro del mercado laboral, por poseer antecedentes penales que, se reflejan con facilidad en las plataformas Estatales, habría que decir, qué se ha patrocinado la metodología cualitativa-cuantitativa, basadas en la entrevista;los resultados nos han concedidointerdisciplinarmente las Personas Privadas de Libertad, Autoridades del Ecuador, hasta el momentoesta problemáticasigue causando mucho dolor, porque, es difícil obtener un empleo digno y seguro, aunque poseen títulos de tercer, cuarto o quinto nivel, estandoen los más altosgrados de desacreditaciónpor haber estado en un proceso,deben de desaparecer de las plataformas Estatales, ya que,toda persona con mucha facilidad consultany los estigmas,concalificativos discriminatorios,nopermite el sistema social ser reintegrados, reinsertados ala sociedad,para poder sobrevivir del fruto ganado, al prohibirles tener una relación laboral,siendoadsorbidospor las grandes estructuras delincuenciales,que los captan dándoles pequeños y grandes encargos que les genera un pago, asiéndose más llevadera su vida, y por ende otra vez,se ven de retorno al bajo mundo delcrimeny delincuencia;
Keywords: Antecedentes penales; Dictamen abstentivo; Auto de sobreseimiento; Rehabilitación social; Reinserción laboral